Code Generation untuk Object Relational Mapping Dengan Menggunakan LINQ dan Text Templating - Rismanto, Ridwan (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
The increase towards Object Oriented Design creates a big gap between OO and relational database. In the other side, relational database still a big favor in designing business-powered application. Developers use Object Relational Mapping (ORM) to fill the gap between OO and RDBMS but still, the problem in the association of RDBMS and OO exists which caused underestimation towards ORM methodology. This research provides a solution to detect relationship inside tables of database, generate LINQ query to map the field of tables to the attribute of the entity classes. Using T4 text templating we are able to generate the whole Data Access Object class which provides transparent encapsulation and relational mapping for the system.Â Keywords : Object Relational Mapping, Relational Database, Object Technology, LINQ, Multi Tier Architecture, Text Templating, T4